Promoting Reversible Dissolution/Deposition of MnO2 for High‐Energy‐Density Zinc Batteries via Enhancing Cut‐Off Voltage. Issue 18 (4th August 2022) - Ruan, Pengchao; Xu, Xilian; Zheng, Dong; Chen, Xianhong; Yin, Xinyu; Liang, Shuquan; Wu, Xianwen; Shi, Wenhui; Cao, Xiehong; Zhou, Jiang
Abstract: Zn//MnO2 batteries based on the MnO2 /Mn 2+ conversion reaction mechanism featuring high energy density, safety, and affordable cost are promising in large‐scale energy storage application. Nonetheless, the continuous H + intercalation at low potential reduces the average output voltage and the energy efficiency, impeding the development of the high‐performance zinc battery. In this work, a strategy was proposed of enhancing the cut‐off voltage from the perspective of electrochemical parameters, toward high energy efficiency and stable output voltage of the Zn//MnO2 battery. This strategy was beneficial to promoting MnO2 dissolution/deposition through the increase of acidity caused by the constant accumulation of MnO2 and inhibiting H + (de)intercalation during cycling process, thereby improving the energy efficiency (83.5 %) along with the stable average output voltage (1.88 V) under the cut‐off voltage of 1.8 V. This work provides a new pathway to promote aqueous zinc batteries with high energy density and stable output voltage. Abstract : Cutting edge : High‐energy‐density Zn//MnO2 batteries are usually plagued by H + (de)intercalation, resulting in low energy efficiency. Here, low potential H + (de)intercalation is suppressed by enhancing cut‐off voltage and promoting the MnO2 dissolution/deposition reaction by the accumulated H +, thus improving the energy efficiency while ensuring high coulombic efficiency. This provides a new research idea for high‐energy‐density zinc batteries.